Testing on performance using robust methods - Zahayu Md. Yusof; Sharipah Soaad Syed Yahaya; Suhaida Abdullah (Monograph series statistics, 2014)
This monograph presents the work on robust procedures when the researchers faced with data that appear to violate the assumption of normality and the data with unbalanced design